Empowerment of the Tourism Sector fot the Economic and Welfare System in Wonodadi Village, Pracimantoro District, Wonogiri Regency - Hardianto, Toni; Rohsulina, Pranichayudha (Journal of Geography Science and Education, 2023)
The empowerment of the tourism sector for the economic and welfare system in Wonodadi Village here requires the role of the local community in its development. Here it can be done through the stages of planning, implementation, and supervision. This study aims to determine the involvement of local communities in empowering tourist villages and this development can have a positive impact on the local community's economic system in Wonodadi Village, including: in the form of increased income for the surrounding community, increased employment and business opportunities for local communities, and increased government revenue through tourist fees. The less dominant role of the government can be utilized by the surrounding community in the development of tourist villages and can increase space for the community to participate. This data collection was carried out using in-depth interviews and questionnaires which were filled in directly by local residents. The analytical method used is SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats).